An Improved Gyrocompass Alignment Method for Large Azimuth Misalignment. (23rd April 2015) - Gao, Wei; Lu, Baofeng; Yu, Chunyang; Lan, Haiyu
Abstract : Due to the impact of the nonlinear factor caused by large azimuth misalignment, the conventional gyrocompass alignment method is hard to favorably meet the requirement of alignment speed under the condition of large azimuth misalignment of INS. In order to solve this problem, an improved gyrocompass alignment method is presented in this paper. The improved method is designed based on the nonlinear model for large azimuth misalignment and performed by opening the azimuth loop. The influence of the nonlinear factor on gyrocompass alignment will be reduced when opening the azimuth loop. Simulation and experimental results show that the initial alignment can be efficiently accomplished through using the improved method in the case of existing large azimuth misalignment, and in the same conditions, the alignment speed of the improved method is faster than that of the conventional one.